Cost of hospitalisation for children with staphylococcus aureus bacteraemia in Western Australia - Miss Keerthi Anpalagan; Dr Anita Campbell; Professor Asha Bowen; Dr Jeffrey Cannon (International Journal of Infectious Diseases)
Introduction: A post-hoc economic analysis including children aged <18 years with confirmed Staphylococcus aureus bacteraemia (SAB) admitted to Perth Children's Hospital (PCH) between Jan 2017 to Dec 2018 was completed. PCH is the largest paediatric tertiary hospital in metropolitan Western Australia. Methodology: There were no intervention nor comparator group. Resource and cost data, including individual patient level data and utilisation data for each episode of SAB hospitalisation was obtained from the PCH Business Intelligence Unit (BIU) for all eligible children. Statistical analyses were performed using STATA version 18. Results: 60 patients with SAB were admitted to PCH and included in the analyses. Forty-five percent were females, 26% identified as Aboriginal and/or Torres Strait Islander and the mean age was 6.63 years. MSSA bacteraemia was the dominant antibiotic susceptibility phenotype (47/61 [77%]). The average cost per index admission was $68,078.34 and the total cost across all patients (n=60) was approximately $4 million. There was a statistically significant difference (p=0.031) in the cost of MRSA bacteraemia (n=11) compared with cost of MSSA bacteraemia (n=46) (MSSA). The median cost of MRSA bacteraemia was $46,798 (IQR, $31,665-$71,938) which was nearly twice the median cost of MSSA bacteraemia ($26,485 [IQR, $12,387-61,456]). Discussion: This study is the first to evaluate hospitalisation cost in paediatric patients with SAB in Australia to better understand the economic burden of paediatric SAB. Further analysis to understand the differences in the MRSA vs MSSA bacteraemia costs must be undertaken. Conclusion: This economic evaluation is crucial for understanding the economic burden of SAB in paediatric patients. It will also play a pivotal role in informing and prioritising paediatric-specific intervention and preventative strategies.